Association Between Individual and Combined SNPs in Genes Related to Innate Immunity and Incidence of CMV Infection in Seropositive Kidney Transplant Recipients. Issue 5 (16th March 2015) - Fernández‐Ruiz, M.; Corrales, I.; Arias, M.; Campistol, J. M.; Giménez, E.; Crespo, J.; López‐Oliva, M. O.; Beneyto, I.; Martín‐Moreno, P. L.; Llamas‐Fuente, F.; Gutiérrez, A.; García‐Álvarez, T.; et al.
Abstract : In this study, we assessed the association between single‐nucleotide polymorphisms (SNPs) in seven candidate genes involved in orchestrating the immune response against cytomegalovirus (CMV) and the 12‐month incidence of CMV infection in 315 CMV‐seropositive kidney transplant (KT) recipients. Patients were managed either by antiviral prophylaxis or preemptive therapy. CMV infection occurred in 140 patients (44.4%), including 13 episodes of disease. After adjusting for various clinical covariates, patients harboring T‐allele genotypes of interleukin‐28B ( IL28B ) (rs12979860) SNP had lower incidence of CMV infection (adjusted hazard ratio [aHR]: 0.66; 95% confidence interval [CI]: 0.46–0.96; p‐value = 0.029). In the analysis restricted to patients not receiving prophylaxis, carriers of the TT genotype of toll‐like receptor 9 (TLR9) (rs5743836) SNP had lower incidence of infection (aHR: 0.61; 95% CI: 0.38–0.96; p‐value = 0.035), whereas the GG genotype of dendritic cell‐specific ICAM 3‐grabbing nonintegrin (DC‐SIGN) (rs735240) SNP exerted the opposite effect (aHR: 1.86; 95% CI: 1.18–2.94; p‐value = 0.008). An independent association was found between the number of unfavorable SNP genotypes carried by the patient and the incidence of CMV infection. In conclusion, specific SNPs in IL28B, TLR9 and DC‐SIGN genes may play a role in modulating the susceptibility to CMV infection in CMV‐seropositive KT recipients. Abstract : Using a large multicenter cohort of seropositive kidney transplant recipients, this study demonstrates the independent effect on the incidence of cytomegalovirus infection of single‐nucleotide polymorphisms in various genes involved in orchestrating innate and adaptive immune responses.